Expression of functional tissue factor in activated T-lymphocytes in vitro and in vivo: A possible contribution of immunity to thrombosis?. (1st September 2016) - De Palma, Raffaele; Cirillo, Plinio; Ciccarelli, Giovanni; Barra, Giusi; Conte, Stefano; Pellegrino, Grazia; Pasquale, Giuseppe; Nassa, Giovanni; Pacifico, Francesco; Leonardi, Antonio; Insabato, Luigi; Calì, Gaetano; et al.
Abstract: Objective: T-lymphocyte activation plays an important role in the pathophysiology of acute coronary syndromes (ACS). Plaques from ACS patients show a selective oligoclonal expansion of T-cells, indicating a specific, antigen-driven recruitment of T-lymphocytes within the unstable lesions. At present, however, it is not known whether T-cells may contribute directly to thrombosis by expressing functional tissue factor (TF). Accordingly, the aim of the present study was to investigate whether T-cells are able to express functional TF in their activated status. Methods: In vitro, CD3 + -cells, isolated from buffy coats, were stimulated with anti-CD3/CD28 beads, IL-6, TNF-α, IL-17, INF-γ or PMA/ionomycin. Following stimulation, TF expression on cell-surface, at gene and protein levels, as well as its procoagulant activity in whole cells and microparticles was measured. In vivo, TF expression was evaluated in CD3 + -cells isolated from the aorta and the coronary sinus of ACS-NSTEMI and stable coronary artery disease (SCAD) patients. The presence of CD3 + -TF +  cells was also evaluated by immunohistochemistry in thrombi aspirated from ACS-STEMI patients. Results: PMA/ionomycin and IL-17 plus INF-γ stimulation resulted in a significant TF increase at gene and protein levels as well as at cell-surface expression. This was accompanied by a parallel increase in FXa generation, both in whole cells and in microparticles, indicating that the induced membrane-bound TF was active. Furthermore, transcardiac TF gradient was significantly higher in CD3 + -cells obtained from ACS-patients compared to SCAD-patients. Interestingly, thrombi from ACS-STEMI patients resulted enriched in CD3 + -cells, most of them expressing TF. Conclusions: Our data demonstrate that activated T-lymphocytes in vitro express functional TF on their membranes, suggesting a direct pathophysiological role of these cells in the thrombotic process; this hypothesis is further supported by the observations in vivo that CD3 + -cells from coronary circulation of ACS-NSTEMI patients show increased TF levels and that coronary thrombi from ACS-STEMI patients are enriched in CD3 + -cells expressing TF.